2013
DOI: 10.1186/1476-0711-12-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characterization of Streptococcus pneumoniae and non-typeable Haemophilus influenzae isolates as primary causes of acute otitis media in Bulgarian children before the introduction of conjugate vaccines

Abstract: BackgroundPneumococcal and Haemophilus influenzae type b (Hib) vaccines were introduced in our national immunisation program in April 2010. The aims of this retrospective, laboratory-based study were to determine the serotypes and antibiotic resistance of Streptococcus pneumoniae and H. influenzae isolates from middle ear fluid (MEF) collected before the introduction of immunization.MethodsS. pneumoniae (n = 128) and H. influenzae (n = 40) strains isolated from MEF of children with AOM between 1994 and 2011 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
4
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
18
4
2
Order By: Relevance
“…It is possible that additional interactions lead to the improved activity against strains with cMLSb compared to the activities of related antibiotics. Nonetheless, it is also reasonable to assume that the changed azi-NN-Cl (1) 0.28 azi-ON-Cl (7) 0.31 azi-ON (8) 0.49 clari-ON-Cl (9) 0.86 claric-NO-Cl (11) 0.73 claric-NO (12) 0.68 azi-OO-Cl (13) 0.58 azi-OO (14) 0.47 claric-OO-Cl (17) 0.87 azi-OON-Cl (19) 0 Inducible macrolide resistance is of strong clinical significance. Depending on the study and the geographical region concerned, macrolide resistance has been detected in 30 to 90% of S. pyogenes isolates (40,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that additional interactions lead to the improved activity against strains with cMLSb compared to the activities of related antibiotics. Nonetheless, it is also reasonable to assume that the changed azi-NN-Cl (1) 0.28 azi-ON-Cl (7) 0.31 azi-ON (8) 0.49 clari-ON-Cl (9) 0.86 claric-NO-Cl (11) 0.73 claric-NO (12) 0.68 azi-OO-Cl (13) 0.58 azi-OO (14) 0.47 claric-OO-Cl (17) 0.87 azi-OON-Cl (19) 0 Inducible macrolide resistance is of strong clinical significance. Depending on the study and the geographical region concerned, macrolide resistance has been detected in 30 to 90% of S. pyogenes isolates (40,52).…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin resistance is predominantly mediated by two mechanisms: ribosome modification by methylation, resulting in a phenotype of inducible resistance to macrolide-lincosamide-streptogramin B (iMLSb) or constitutive resistance to macrolide-lincosamide-streptogramin B (cMLSb), and the production of efflux pumps, resulting in the M phenotype. In addition, pneumococcal isolates with mutations in 23S rRNA domains II and V and ribosomal proteins L4 and L22 have been reported, but their clinical significance is still rather low (10)(11)(12)(13). In Streptococcus pyogenes, inducible erm gene expression has three distinct patterns with different levels of resistance to macrolides with a 14-, 15-, or 16-membered macrolactone ring (14).…”
mentioning
confidence: 99%
“…Studija o osetljivosti pneumokoka izazivača AOM u Bugarskoj iz 2014. godine prikazala je 28,1% rezistentnih izolata (12). U zemljama Mediterana, gde su stope rezistencije pneumokoka na antibiotike bile tradicionalno visoke, beleži se pad nakon uvođenja obavezne pneumokokne vakcine.…”
Section: Diskusijaunclassified
“…Nešto nižu incidenciju rezistencije prikazuju okolne zemlje, Bugarska (46,9%), Rumunija (58,3%) i Hrvatska (37%) (12,14,11). Do sada je već opisana pojava da rezistencija streptokoka na makrolide raste sa većom potrošnjom ovih antibiotika (15).…”
Section: Diskusijaunclassified
“…Streptococcus pneumoniae and Haemophilus influenzae have been consistently reported to be the two major bacterial pathogens responsible for AOM, mainly by studies in the USA and European countries [5][6][7]. Three pneumococcal conjugate vaccines (PCVs) are currently licensed for use in children and they have showed modest efficacy against AOM overall [8]. Randomized clinical trials with a 7-valent pneumococcal conjugate vaccine (PCV-7) in the USA and Finland showed reductions in the incidence of AOM of 6-9% [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%